Facile synthesis of 2D ultrathin and ultrahigh specific surface hierarchical porous carbon nanosheets for advanced energy storage. (December 2019) - Yao, Yuechao; Xiao, Zunqin; Liu, Peng; Zhang, Shengjiao; Niu, Yuan; Wu, Hongliang; Liu, Shiyu; Tu, Wenxuan; Luo, Qi; Sial, Muhammad Aurang Zeb Gul; Zeng, Shaozhong; Zhang, Qi; et al.
Abstract: Two dimensional (2D) porous carbon nanosheets (CNS) have attracted tremendous research interests in energy storage and conversion, such as supercapacitors (SCs) and lithium-sulfur batteries, because of their unique micromorphology, chemical stability and high specific surface area (SSA). Rational design and facile scalable synthesis of CNS with high SSA, low cost and ultrathin nanosheet structure is highly desired but hitherto remains a big challenge. Here, we report a novel synthesis method of 2D hierarchical porous CNS with ultrahigh SSA (2687 m 2 g −1 ) and ultrathin structure by directly pyrolysing and activating a unique and abundant biomass sheet. The electrochemical characterisations show that the prepared CNS-4-1 materials as electrodes creates a good energy-storage capability, with the energy density being 91 Wh kg −1 for symmetric SCs in ionic liquids, which is the highest in the reported biomass-derived CNS materials for SCs applications so far. Besides, the CNS-5-1 also exhibits a high initial capacity of 1078 mAh g −1 at 0.1 C when it acted as a sulfur hosting material for lithium-sulfur batteries. More importantly, it also shows a 586 mAh g −1 reversible capacity and an approaching 100% coulombic efficiency after 500 cycles at a high rate of 1 C. These superior electrochemical properties of the CNS are mainly attributed to their unique 2D ultrathin nanosheet structure, large SSA, and reasonable hierarchical porous structure. This work not only provides a new strategy to fabricate the ultrathin CNS in large scale and low cost but also enlarges CNS materials potential applications in energy storage. Graphical abstract: Here, we report a novel synthesis method of 2D hierarchical porous CNS with ultrahigh SSA (2687 m 2 g -1 ) and ultrathin structure (4 nm) by directly pyrolysing and activating a unique and abundant biomass sheet. The electrochemical characterisations show that the prepared CNS-4-1 materials as electrodes creates a good energy-storage capability, with the energy density being 91 Wh kg −1 for symmetric SCs Besides, the CNS-5-1 also exhibits a high initial capacity of 1078 mAh g -1 at 0.1C when it acted as a sulfur hosting material for lithium-sulfur batteries. More importantly, it also shows a 586 mAh g -1 reversible capacity after 500 cycles at a high rate of 1 C. Image 1